Are the kidneys involved in lipoid proteinosis? Study of 22 patients. Issue 8 (17th May 2021) - Yilmaz, Kenan; An, Isa; Sahin, Suleyman; Sahutoglu, Tuncay
Abstract: Aim: Lipoid proteinosis (LP) is a systemic, progressive, rare genodermatosis that manifests in early life with mucocutaneous lesions. Kidney involvement has not been described before, hence we aimed to investigate kidney findings in LP patients. Materials and Methods: In this cross‐sectional study, LP patients who were followed up and diagnosed with clinical, histopathological and radiological findings in the Dermatology outpatient clinic were invited to the Pediatric Nephrology Clinic. Biochemical, spot urine and 24‐hour urine collection tests and ultrasound scans were scanned for the functional and anatomical status of the kidneys. Healthy controls who visited the Pediatric Nephrology Clinic during study periods for other reasons were invited to participate as the control group. Results: Data of 44 participants (22 LP patients, mean age 14.5 years and 22 healthy controls, mean age 14.3 years) were available for the analysis. Ultrasound scans revealed simple renal cysts in 68% of LP patients. The cysts were bilateral in 4 patients, while no cyst was detected in healthy controls. Biochemical parameters, proteinuria, and albuminuria were all within the normal reference range in both LP patients and healthy controls, whereas LP patients had statistically significant lower serum albumin and higher C‐reactive protein levels than healthy controls. Conclusion: Multiple simple renal cysts were detected in the majority of LP patients, and this finding could be part of the systemic involvement of the disease. Renal functions and biochemical parameters were within the normal reference range, but low serum albumin and high C‐reactive protein levels in LP patients may be the signs of elevated systemic inflammation. Although more studies are needed to better define these findings, the presence of many simple renal cysts in LP patients was found to be the most important finding of this study.